Synthetic microplastic abundance and composition along a longitudinal gradient traversing the subtropical gyre in the North Atlantic Ocean. (December 2022) - Courtene-Jones, Winnie; van Gennip, Simon; Penicaud, Juliette; Penn, Emily; Thompson, Richard C.
Abstract: Plastic pollution has been reported in the North Atlantic Ocean since the 1970s, yet limited data over subsequent decades pose challenges when assessing spatio-temporal trends in relation to global leakages and intervention strategies. This study quantified microplastics within the upper ocean along a longitudinal transect of the North Atlantic and its subtropical gyre. Microplastics were sampled from surface and subsurface (−25 m) water using a manta trawl and NIKSIN bottle respectively. The surface water polymer community varied significantly between geographic positions ('inshore', 'gyre', 'open ocean'), and was significantly influenced by fragment quantity. Compared to other positions, the North Atlantic gyre was associated with high concentrations of polyethylene, polypropylene, acrylic and polyamide fragments. Subsurface water was dominated by polyamide and polyester fibres. Backtracked 2-year Lagrangian simulations illustrated connectivity patterns. Continued monitoring of microplastics throughout the water column of the North Atlantic Ocean is required to address knowledge gaps and assess spatio-temporal trends. Graphical abstract: Unlabelled Image Highlights: MPs sampled from the upper ocean across longitudinal transect of N. Atlantic Ocean Polymer community significantly varied geographically. Significantly greater quantity of fragments in N. Atlantic gyre than other regions PA and polyester fibres predominantly isolated from subsurface water (25 m). Ongoing study of the N. Atlantic required to examine spatio-temporal plastic trends.